2005
DOI: 10.1261/rna.2238705
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that ribavirin interacts with eIF4E

Abstract: This commentary discusses the recent reports in RNA by Yan and colleagues and Westman and colleagues of the apparent failure of ribavirin to bind to recombinant eIF4E and inhibit 7-methyl guanosine cap-dependent exogenous mRNA translation of cell extracts in vitro. Measuring binding by using affinity chromatography of matrix-immobilized proteins and by using protein emission fluorescence spectroscopy in the presence of nucleotide ligands, as well as limitations of using cell extracts for the assessment of mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 21 publications
6
82
0
Order By: Relevance
“…142 The antiviral drug ribavirin can block the binding of eIF4E to mRNA. [143][144] The effects of this compound were examined in some patients with relapsed M4/M5 AML who were no longer eligible for chemotherapy. Although the number of patients in this preliminary trial were low (n ¼ 11), one complete and two partial responders were observed.…”
Section: -112mentioning
confidence: 99%
“…142 The antiviral drug ribavirin can block the binding of eIF4E to mRNA. [143][144] The effects of this compound were examined in some patients with relapsed M4/M5 AML who were no longer eligible for chemotherapy. Although the number of patients in this preliminary trial were low (n ¼ 11), one complete and two partial responders were observed.…”
Section: -112mentioning
confidence: 99%
“…149 The antiviral drug ribavirin can block the binding of eIF4E to mRNA. 150,151 Thus, the effects of this compound were examined in some patients with relapsed M4/M5 AML who were no longer eligible for chemotherapy. Although the number of patients in this preliminary trial were low (n ¼ 11), one complete and two partial responders were observed.…”
Section: Pi3k/pten/akt/mtor Drug Resistance and Leukemia Therapymentioning
confidence: 99%
“…Ribavirin directly binds eIF4E as observed by NMR and mass spectrometry experiments. 31,34 Further, ribavirin impedes both eIF4E's function in 4E-SE mRNA export and in translation of eIF4E sensitive transcripts. 31 Consistent with its biochemical activity, ribavirin inhibits the growth promoting activities of eIF4E.…”
Section: Rna Regulons As Therapeutic Targetsmentioning
confidence: 99%
“…38 Ribavirin provides an alternative strategy to target eIF4E activity as it directly targets eIF4E via its mimicry of the m 7 G cap. 31,34 Thus, it is positioned to efficiently shut down the eIF4E regulon. However, only future clinical studies will determine its value in cancer therapies.…”
Section: Rna Regulons As Therapeutic Targetsmentioning
confidence: 99%